ANALISA PENGARUH KETINGGIAN BAK PENANGKAP AIR DAN BERAT KATUB BUANG TERHADAP HEAD PUMP PADA POMPA HIDRAM - Utomo, Gatut Prijo; Ali Aziz, Moh. Nor (MEKANIKA: Jurnal Teknik Mesin, 2015)
Ketos Hamlet and Hamlet Cabe is 2 (two) of 7 (seven) Dudun Village Wonodadi Kulon Ngadirojo Pacitan, East Java. The problems faced by the community, especially for Ketos Hamlet and Hamlet Cabe whose territory theform of hills and rocks are prone / difficulty of clean water, clean water to meet the needs of the people using waterfrom springs and rainwater. In the dry season, water from springs debitnya reduced, so that less water needs in thevillage. Only water can not be drained using gravity because it is under the township residents located on the hill -a hill at an altitude of 750 m above sea level. The approach offered to solve the problem is by making a catchmentbasin, hydraulic ram and tank water divider.The effectiveness of the performance of hydraulic ram is influenced by several parameters, among others: the lengthof the inlet pipe, inlet pipe diameter, high penagkap tub of water, and heavy exhaust valve. This study aims toobserve and analyze the effect of altitude penagkap tub of water and heavy exhaust valve on the hydraulic ram pumphead. Methods of research through design and analyze hydraulic ram catcher height tub water is 3.5 m, 3 m and 2.5m and weight of the exhaust valves 16.6 N (1.7 kg), 21.6 N (2.2 kg) and 26.5 N (2.7 kg). Tests carried out in theriver, precisely in Hamlet and Hamlet Ketos Cabe, Pacitan.From the results of the data collection high catchment basin 3.5 m and weight of the exhaust valves 26.5 N (2.7 kg)with a height h = 180 m has a maximum pressure of other testing and discharge of produced water is 7.5 L / min. Sothe higher the catcher bath water (H) the higher the pressure generated in the intake, due to the greater mass andvelocity, the momentum is also getting bigger. As for the valve exhaust (w) with a heavy load and stride lengthconsiderable allow fluid to flow more quickly, so that when the valve sewage closing will surge high enoughpressure that makes impulse flow is greater exceeds the static pressure inlet pipe, and the may result in elevatedworking fluid toward the air tube. And it has an effect on the hydraulic ram pump head.Keywords: hydraulic ram, high penagkap tub of water, the weight of the exhaust valve